Interreligious Dialogue in Public Service Broadcasting. A Case Study in Catalonia (Spain) - Amparo Huertas Bailén (Religions, 2020)
This text addresses how the media deals with interreligious dialogue based on the case study of the Catalan public television stations. Our theoretical framework revolves around the concept of mediation, which is regarded as a communicative concept that emphasizes the socializing power of the mass media as well as its potential contribution to social cohesion. A quantitative and qualitative analysis is presented of a sample of 41 multi-religious audiovisual pieces broadcast between 2015 and 2018, which were located in the Corporation’s on-demand online service. The religious diversity that currently exists in European cities is reflected in the media content. Although it is true that the Catholic religion features in 63% of the sample, it only becomes the focal point on less than half of the occasions in which it appears. The religious options with more presence are Catholicism in relation to Islam and atheism in relation to Catholicism, but these cases only account for 26.8% of the sample. Interreligious dialogue appears as the main focus of the discourse in only 14.6% of the sample and, in general, the tendency towards a Euro-Catholic-centric discourse has been detected.